Atypical Inter‐Network Deactivation Associated With the Posterior Default‐Mode Network in Autism Spectrum Disorder. Issue 2 (18th November 2020) - Kotila, Aija; Järvelä, Matti; Korhonen, Vesa; Loukusa, Soile; Hurtig, Tuula; Ebeling, Hanna; Kiviniemi, Vesa; Raatikainen, Ville
Abstract : Previous studies have suggested that atypical deactivation of functional brain networks contributes to the complex cognitive and behavioral profile associated with autism spectrum disorder (ASD). However, these studies have not considered the temporal dynamics of deactivation mechanisms between the networks. In this study, we examined (a) mutual deactivation and (b) mutual activation‐deactivation (i.e., anticorrelated) time‐lag patterns between resting‐state networks (RSNs) in young adults with ASD ( n = 20) and controls ( n = 20) by applying the recently defined dynamic lag analysis (DLA) method, which measures time‐lag variations peak‐by‐peak between the networks. In order to achieve temporally accurate lag patterns, the brain imaging data was acquired with a fast functional magnetic resonance imaging (fMRI) sequence (TR = 100 ms). Group‐level independent component analysis was used to identify 16 RSNs for the DLA. We found altered mutual deactivation timings in ASD in (a) three of the deactivated and (b) two of the transiently anticorrelated (activated‐deactivated) RSN pairs, which survived the strict threshold for significance of surrogate data. Of the significant RSN pairs, 80% included the posterior default‐mode network (DMN). We propose that temporally altered deactivation mechanisms, including timings and directionality, between the posterior DMN and RSNs mediating processing of socially relevant information may contribute to the ASD phenotype. Lay Summary: To understand autistic traits on a neural level, we examined temporal fluctuations in information flow between brain regions in young adults with autism spectrum disorder (ASD) and controls. We used a fast neuroimaging procedure to investigate deactivation mechanisms between brain regions. We found that timings and directionality of communication between certain brain regions were temporally altered in ASD, suggesting atypical deactivation mechanisms associated with the posterior default‐mode network.